Preferensi Masyarakat dalam Penggunaan BRT yang Adaptif Pandemi - Sugiyarto, Anis Meilitasari; Widjonarko, Widjonarko (Jurusan Perencanaan Wilayah dan Kota, 2024)
The Bawen-Tawang Bus Rapid Transit (BRT) is urban public transportation in Central Java that experienced a decline in passengers due to the 2020–2021 pandemic. The risk of the new pathogen disease X creating a negative pandemic for public transportation is because it is transmitted through the air and physical contact. This research aims to measure the preferences of the pandemic-adaptive Bawen-Tawang BRT based on stated preferences. Data collection was carried out using a questionnaire survey of eight service scenarios for 100 users using non-probability accidental techniques and quantitative descriptive analysis, including descriptive statistics, logistic regression, and binomial logit models. The results show that there is a change in the preferences of Bawen-Tawang BRT users if the BRT service becomes pandemic-adaptive. The most preferred scenario is service 6 by 94.34% of respondents and scenario 2 by 93.12%, which is 1.22% different due to differences in subsidized rates for service 2. Both services are in accordance with user characteristics. 79% have never had respiratory illnesses, 44% are quite worried about pandemics, rates are not important for 48% of users, and 42% are willing to pay according to the new policy. Safety assurance influenced preferences 4,305 times and adaptive services 4,039 times.